Fetal diagnosis of Mowat‐Wilson syndrome by whole exome sequencing. Issue 10 (19th July 2019) - Evans, Carey‐Anne; Pinner, Jason; Chan, Cheng Y.; Bowyer, Lucy; Mowat, David; Buckley, Michael F.; Roscioli, Tony
Abstract: Mowat‐Wilson syndrome (MWS) is a complex genetic disorder associated with heterozygous variation in ZEB2 . It is mainly characterized by moderate‐to‐severe intellectual disability, facial dysmorphism, epilepsy, and various malformations including Hirschsprung disease, corpus callosum anomalies, and congenital heart defects. It is rarely diagnosed prenatally and there is limited information available on the prenatal phenotype associated with MWS. Here we report the detection of a heterozygous de novo nonsense variant in ZEB2 by whole exome sequencing in a fetus with microphthalmia in addition to cardiac defects and typical MWS facial dysmorphism. As the prenatal phenotypic spectrum of MWS expands, the routine addition of fetal genomic testing particularly in the presence of multiple malformations will increase both the sensitivity and specificity of prenatal diagnostics.